Validation of Thwaites index for diagnosing tuberculous meningitis in a Colombian population (2016)
ABSTRACT : Objective.: To determine the diagnostic accuracy of Thwaites Index (TI) in a Colombian population to distinguish meningeal tuberculosis (MTB) from bacterial meningitis (BM) and from non-tuberculous meningitis. Exploratory analyses were conducted to assess the TI's validity for patients with human immunodeficiency virus (HIV) and children above six-years-old. Methods: The study included 527 patients, the TI was calculated and results compared with those of a reference standard established by expert neurologists. Sensitivity, specificity, area under the curve of receiver-operator characteristics (AUC-ROC) and likelihood ratios were calculated. Results: The AUC-ROC to distinguish MTB from non-tuberculous meningitis was 0.72 (95% CI: 0.67–0.77) for HIV negative adults. AUC-ROC was 0.62 (95% CI: 0.50–0.74) for HIV positive adults and 0.83 (95% CI: 0.68–0.97) for children. For distinguishing MTB from BM the AUC-ROC was 0.78 (95% CI: 0.73–0.83); furthermore, the AUC-ROC was 0.57 (95% CI: 0.31–0.83) for HIV positive adults and 0.86 (95% CI: 0.73–0.99) for children. Conclusion: The TI was sensitive but not specific when used to distinguish MTB from BM in HIV negative adults. In HIV positive adults the index had low diagnostic accuracy. Moreover, the TI showed discrimination capability for children over 6 years; however, research with larger samples is required in these.